Diabetic Ketoacidosis as The First Manifestation of a Young Adult with Diabetes A Clinical Approach to Distinguish Different Types of Diabetes Mellitus - M. Ikhsan Mokoagow; Anak Agung Arie Widiastuti; Jerry Nasarudin; Marina Epriliawati; Ida Ayu Made Kshanti; Nobian Andre; Adlina Hafidzati; Vania Tryanni (‎ InaJEMD - Indonesian Journal of Endocrinology Metabolic and Diabetes, 2024)
Diabetic ketoacidosis (DKA) is an acute metabolic complication of diabetes. While it most commonly occurs in type 1 diabetes (T1DM), DKA can also occur in other types of diabetes. Encountering a case of DKA prompts further evaluation to determine the type of diabetes and manage patients accordingly. To establish a diagnosis of the type of diabetes in a case with an unusual presentation of DKA through a clinical approach. A 30-year- old male presented to the emergency department with sudden dyspnea. Laboratory examinations showed a blood glucose level of 506 mg/dL, a blood ketone level of 2.6 mmol/L, and a bicarbonate level of 5 mEq/L. Hishemoglobin A1c was 15.3%. He had not been previously diagnosed with diabetes mellitus. Studies have shown overlapping clinical and biochemical parameters of DKA among various types of diabetes. Following life-saving management, further clinical and laboratory evaluations should be performed. Measurement of autoantibody titer (i.e.: autoantibodies against glutamic acid decarboxylase, islet antigen-2, zinc transporter 8, and insulin) and c-peptide levels might help determine the type of diabetes in this patient. Establishing the diagnosis of a certain type of diabetes in young adults can be challenging. Based on clinical profile, a presumptive diagnosis of autoimmune diabetes, particularly latent autoimmune diabetes in adults (LADA), was made in this patient.